Adjuvant chemoradiotherapy versus radiotherapy in cervical cancer patients with intermediate-risk factors: A systematic review and meta-analysis. (July 2019) - Li, Meng; Hu, Mengyang; Wang, Yuanjian; Yang, Xingsheng
Abstract: Background: At present, extensive hysterectomy and pelvic lymph node dissection are preferred for early-stage cervical cancer. However, additional adjuvant therapy could be considered if there is a risk for recurrence. Postoperative pelvic radiotherapy plus concurrent platinum-based chemotherapy are recommended for patients with high risk factors. The treatment regimen for patients with intermediate-risk factors, however, remains unclear. We, thus, performed a systematic review and meta-analysis to assess the recurrence-free survival (RFS), overall survival (OS), grade III/IV hematologic toxicity and grade III/IV non-hematologic toxicity in chemoradiotherapy (CRT) versus radiotherapy (RT) groups. Methods: We systematically searched PubMed, Cochrane, and Embase to identify relevant studies published before November 30, 2018 to compare CRT with RT as a postoperative adjuvant therapy in early-stage cervical cancer patients with intermediate-risk factors. We used Stata (version 14.0) to calculate odds risks (ORs) and 95% confidence intervals (CIs) and pooled data was assessed by the fixed-effects model. Results: Of the 428 identified studies, only 9 were eligible and included in our analysis (CRT: n = 870; RT: n = 932). CRT significantly prolonged RFS (OR = 3.43, 95% CI 2.08–5.67, P = 0.000) and OS (OR = 1.80, 95% CI 1.30–2.50, P = 0.000). The occurrence rate of grade III/IV hematologic toxicity (OR = 16.07, 95% CI 6.47–39.93, P = 0.000) was significantly higher in CRT, while grade III/IV non-hematologic toxicity was ambiguous for CRT and RT with an OR of 1.91 (95% CI 0.95–3.83, P = 0.069). Conclusions: For early-stage cervical cancer patients with intermediate-risk factors, CRT can dramatically improve RFS and OS compared with RT. Apart from the increase in grade III/IV hematologic toxicity, CRT was well tolerated and accepted treatment for early-stage cervical cancer.